A Verdant Ethnography: Henry Green, Navajo Poetry, and Dialogical Ethnopoetics - Webster, Anthony (Anthropologica, 2023)
The endeavour here is to write an ethnography with a sense of living. Using the literary work and theories of Henry Green, as well as concerns with dialogical anthropology, a discourse-centred approach to language and culture (conjoined here as a dialogical ethnopoetics), and Navajo rhetorical practices, I present an aggregate of transcripts from several conversations with Navajo poets over the years. It is the transcripts that give life to ethnography. The first part places this endeavour in an intellectual context; the much longer second part gives the verdant ethnography. A verdant ethnography is predicated on an empirical foundation (transcripts), but also on an obliqueness as well (the stuff of talk).